Examining emergent active learning processes as transformative praxis : the case of the schools and sustainability professional development programme - Schudel, Ingrid Joan (Rhodes University, Faculty of Education, Department of Education, 2013)
This is a study on the nature of learning, particularly the emergence of active learning processes in the case of an environmental education teacher professional development programme "“ the Eastern Cape Border-Kei cohort of the 2008 Schools and Sustainability Course. This was a part-time, one-year course supporting teachers to qualify, strengthen and deepen opportunities for environmental learning in the South African curriculum. An active learning framework (O'Donoghue, 2001) promoting teaching and learning with information, enquiry, action and reporting/reflection dimensions was integrated into the Schools and Sustainability course design to support these environmental learning opportunities. In this study, the notion of active learning is elaborated as a situated, action-oriented, deliberative and co-engaged approach to teaching and learning, and related to Bhaskar's (1993) notion of transformative praxis. The study used a nested case study design, considering the case of six Foundation Phase teachers in six primary schools within the Border-Kei Schools and Sustainability cohort. Interviews, observations (of workshops and lesson plan implementation in classrooms) and document review of teacher portfolios (detailing course activities, lesson plans, learners' work and learning and teaching support materials) were used to generate the bulk of the data. A critical realist theory underpinning the methodology enables a view of agency as emergent from social structures and mechanisms as elaborated in Archer's (1998b) model of morphogenesis and Bhaskar's (1993) model of four-planar being. The critical realist methodology also enables a view of emergent active learning processes as open-ended, responsive to particular potential, but dependent on contingencies (such as learning and teaching support materials, tools and methodologies). The analysis of emergent active learning processes focuses particularly on Bhaskar's (1993) ontological-axiological chain (MELD schema) as a tool for analysing change. The MELD schema highlights1M ontological questions of what is (with emphasis on structures and generative mechanisms) and what could be (real, but non-actualised possibilities). It enables reflection on what mediating and interactive agential processes either reproduce what is or have the potential to transform what is to what could be (2E). Thirdly, the MELD schema enables reflection on what should be "“ this is the 3L "axiological moment" (Bhaskar, 1993: 9) where questions of values and ethics in relation to the holistic whole are raised. Finally, the schema raises questions (4D) of what can be, with ontologically grounded, context-sensitive and expressively veracious considerations. The study describes the agency of course tutors, teachers and learners involved in the Schools and Sustainability course, as emergent from a social-ecological context of poverty and inequality, and from an education system with a dual transformative and progressive intent (Taylor, 1999). It uses a spiral approach to cluster-based teacher professional development (Janse van Rensburg & Mhoney, 2000) focusing on the development of autonomous (Bernstein, 1990) and reflexive teachers. With teachers well-disposed and qualified to fill a variety of roles in the classroom, these generative structures and mechanisms had the power to drive active learning processes with potential for manifestation as transformative praxis. Through the analysis of the active learning processes emergent from this context, the study shows that the manifestation of transformative praxis was contingent on relational situated learning, value-based reflexive deliberations, and an action-orientation with an emphasis on an iterative relationship between learning and doing. These findings enable a reframing of an interest in action in response to environmental issue and risk, to an interest in the processes that led up to that action. This provides a nuanced vision of active learning that does not judge an educational process by its outcome. Instead, it can be judged by the depth of the insights into absences (2E), the ability to guide moral deliberations on totality (3L), and by the degree of reality congruence (1M) in the lead up to the development of transformative agency (4D). The study also has a methodological interest. It contributes to educational and social science research in that it applies dialectical critical realist philosophy to a concrete context of active learning enquiry in environmental education. It reports on the value of the onto-axiolgical chain in describing a diachronic, emergent and open-ended process; in providing ontological grounding for analysis (1M); in understanding relationality in situated learing processes (2E); in focusing on value-based reflexive learning (3L) and in understanding transformative learning as "tensed socio-spatialising process" (Bhaskar, 1993: 160) where society is emergent from a stratified ontology, and agency and change are open-ended and flexible processes not wholly determined by the social structures from which they emerge (4D). Considering the knowledge interests defined in the 2011 South African Minimum Requirements for Teacher Education (South Africa. Department of Higher Education and Training, 2011) and the Curriculum Assessment Policy Statements (CAPS) which were implemented in South Africa from 2012 (in a phased approach), the study concludes with recommendations for exploring environmental learning in the CAPS. The study proposes working with a knowledge-focused curriculum focusing on the exploration and deepening of foundational environmental concepts, developing relational situated learning processes for meaningful local application of knowledge, supporting transformative praxis through the "unity of theory and practice in practice" (Bhaskar, 1993: 9), and implementing a spiral approach to cluster-based teacher professional development.
Keywords: Active learning -- Study and teaching (Elementary) -- South Africa -- Eastern Cape; Student-centered learning -- Research -- South Africa -- Eastern Cape; Environmental education -- Study and teaching (Elementary) -- South Africa -- Eastern Cape; Environmental education -- Curricula -- South Africa -- Eastern Cape; Competency-based education -- South Africa -- Eastern Cape; Teachers -- Training of -- South Africa -- Eastern Cape